Geopolitical dimensions of the cinematic image in the films of the Palestinian cause (Al-Academy, 2021)
For more than seven decades, the Palestinian-Israeli conflict has not ended, and every one claims his right to the land, waters, airspace and wealth of Palestine. This conflict was reflected in the political, military, social and cultural aspects, and the cinema had a prominent role in conveying messages to the world about this conflict. On the geopolitical dimensions and their impact on the cinematic image in the films of the Palestinian cause), the researchers divided the research into four frameworks that came as follows: (methodological framework) and included the research problem, its importance, research objectives, research limits and sealing the chapter by defining the terms. And (theoretical framework): it was divided into two sections: the first topic: the relationship of art to politics, the second topic: films of the Palestinian cause, and the researchers came up with a number of indicators. (Research procedures): It includes: the research method, the research community, the research sample, and the movie (The Embassy in Architecture) was selected, the research tool, the validity of the tool, and the sample analysis, (Results and Conclusions): The research results and conclusions included:1. The movie is one of the means of communication that affects the masses and changes their attitudes.2. Film can be considered as an educational means to convey ideas and convictions to the recipient.He concluded with recommendations, sources and references